53 Case report: hip fracture at the end of life – guiding patients' choice of operative or non-operative palliation. (14th March 2023) - Muir, David; Johansen, Antony; Rawlinson, Fiona
Abstract : We are presenting this case as a late abstract owing to the time of presentation and the learning that arose from it. A 70-year-old man with T4b N3 M0 poorly differentiated squamous cell carcinoma of the oesophagus was referred to the Community Palliative Care Team. His preferred place of care and death were home and he requested not to receive CPR, although open to hospital admission for reversible causes. His condition deteriorated with intermittent delirium and agitation, making home care challenging. He was admitted to the local Cancer Centre as no beds were available in the local Hospice inpatient unit and suffered a witnessed fall on a Sunday. Examination revealed a shortened and externally rotated left leg and inability to weight bear. Pelvic XR demonstrated a left displaced intracapsular hip fracture. The patient was discussed with the on-call Orthopaedic Registrar who advised that the patient would be discussed in the regular trauma meeting on Monday and should remain in the Cancer Centre. On Tuesday, in order to avoid admission to the local Major Trauma Centre, the patient was visited in the Cancer Centre by the Consultant Orthogeriatrician. After consultation with the patient and his family, it was agreed that he did not need surgery and that his hip fracture could be managed conservatively with bed-rest and analgesia. The patient was transferred to the Hospice on Tuesday and felt to be in the last days of life 24-hours later. The patient's pain was managed effectively with a continued subcutaneous infusion with Morphine and Midazolam. The patient continued to steadily deteriorate and peacefully died on Saturday. Discussion: Orthogeriatricians now lead the acute peri-operative care and rehabilitation of hip fracture patients in every acute trauma unit in the UK. This case demonstrates how early discussion of complex patients with an Orthogeriatrician can help the patient, oncology and palliative care teams to make the right choice of available operative and non-operative options, and avoid inappropriate hospital transfers.